Theorizing an Early Childhood Educator’s Authority for the Advancement of Social Goods - Langford, Rachel (Alberta Journal of Educational Research, 2010)
Authority is an uncomfortable subject for early childhood educators. This article outlines some tensions between the theory and practice of an early childhood educator’s authority and the implications of these tensions for educators themselves and the social changes they envisage. Drawing on a range of feminist educational philosophers and critical pedagogy theorists, critiques of both traditional authority and a rejection of authority are examined. A description is offered of an early childhood educator’s authority that emerges from the actualities of pedagogical experiences and relationships and that can influence and instigate action for social goods.